Conceptual Reconstruction of Legal Diversity in the National Legal System as an Effort to Realize Substantive Justice in a Multicultural Society - Lorraine Rangga Boro; Suparno (Indonesian Journal Publisher, 2026)
This study aims to reconstruct the conceptualization of legal diversity in the national legal system as an effort to realize substantive justice in Indonesia's multicultural society, however, in legislative and judicial practice, the legal centralism paradigm and positivistic approach still dominate, which places state law as the sole normative authority. The study employs a normative juridical method, utilizing a statutory and conceptual approach, to analyze the normative construction of legal pluralism, the problems of norm conflict and regulatory disharmony, and the inconsistency in the recognition of customary law and religious law in judicial practice. The study results indicate that the recognition of legal diversity remains sectoral and conditional, and as a result, it has been unable to guarantee substantive justice for vulnerable groups. This research proposes a model of constitutional legal pluralism based on the Pancasila Rule of Law, which positions the constitution as the meeting point for harmonizing state and non-state law and restructuring the relationship between legal certainty and substantive justice within the national legal system.